Nije lako s muškarcima . It Isn’t Easy to Get Along with Men - Vukobratović, Mihailo (Avala Pro-Film Beograd, 1985)
The movie evolves around the life of a divorced mother and her three teenaged daughters. The mother has a hard time in balancing the roles of working woman and good parent, while keeping a good relationship with her ex-husband. The introduction finds her delighted as for the first time in years she plans to go alone on a summer holidays to the sea, since her daughters have other plans. But their plans change and she ends up leaving for the seaside together with all of her daughters. The vacation does not get much better as they are forced to stay in the auto-camp, and the news arrives that her ex-husband is getting married again. When it seems that her vacation has hit rock bottom, she meets a handsome divorced doctor and they fall in love. Not accustomed to having a man beside her, she finds it hard to break the news to her daughters, especially as the oldest one has also fallen in love with the same person. New problems emerge with the arrival of a rich American who hits on her, but eventually, everything ends happily and the mother marries her doctor.